THE ROLE OF VIRTUAL YOUTUBER KOBO KANAERU AS AN INFLUENCER IN TOKOPEDIA’S WAR CAMPAIGN - Cattleya Rejito; Mochammad Chairul Ihsan; Wahyu Arif Firmansyah (Journal of Innovation Research and Knowledge, 2025)
This study explores the role of Kobo Kanaeru, a Virtual YouTuber (VTuber) associated with Hololive Indonesia, as an influencer in Tokopedia’s WAR campaign. Utilizing the source credibility model, the research examines the influence of three key attributes—Expertise, Trustworthiness, and Attractiveness—on consumer Purchase Intention. A quantitative approach using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed to analyze data collected from 100 respondents aged 18–27 years, who were exposed to the WAR Tokopedia campaign. The results demonstrate that while Expertise, Trustworthiness, and Attractiveness significantly contribute to Purchase Intention, their individual effects are relatively weak, with path coefficients of 0.040, 0.040, and 0.041, respectively. The model explains 32.4% of the variance in Purchase Intention, highlighting the need for incorporating additional variables such as emotional connection and brand reputation. This study provides insights into the strategic advantages and challenges of using virtual influencers in digital marketing and recommends future research directions to optimize their effectiveness.